Três ensaios sobre o mercado de trabalho no Brasil - Zylberstajn, Eduardo (2015)
This dissertation explores in three essays and one short note different issues related to the Brazilian Labor Market. The first chapter extends the traditional literature on flows into and out of unemployment (as in Shimer, 2012) by accounting for two different types of employment: formal and informal. Results suggest that the standard three-state approach is insufficient for a full understanding of the labor market dynamics witnessed in the past decade in Brazil, since it overstates the contribution of the employment exit rate to the change in unemployment. When disentangling formal and informal work, it is shown that the main drivers of the decline in the unemployment rate between 2003 and 2014 were (in order of relevance): (i) the decline in the participation rate that happened due to a decrease in the entries into the workforce (from inactivity); (ii) the increase in the formal job finding rate and (iii) the decline in the inflow from formal employment into unemployment. The second chapter investigates the causal effect of education on earnings in Brazil by employing a new method that does not need first order exclusion restrictions. This approach yields unbiased estimates in the absence of instruments and allows for interpretation of the coefficients that is not confined to local average treatment effects. Results indicate that the return to schooling is downward biased in OLS estimates. The third chapter investigates wage differentials between outsourced and directly hired employees. The findings show that unobservable characteristics account for most of the difference and that low skill occupations tend to impose higher penalties on wages for outsourced workers. Finally, chapter force presents a short note documenting two relevant aspects of the Monthly Employment Survey (Pesquisa Mensal de Emprego/IBGE)that are usually neglected by researchers but may lead to imprecise results if not properly accounted for